Food Design and Film Art in the Preservation of Ethnic Culture - Valeri I. Kukenkov (Publishing house "Sreda", 2020)
The author outlines that the study of food design and film art as part of the country's ethnic culture examines the preservation and development of traditions and interethnic ties. Given that folk traditions have a peculiarity to develop, being in constant search of new solutions, taking into account the emergence of new materials, technologies and information tools, an idea to combine the potential of film art and food design in research has started up. It is noted that the search for analogues of the issue studied has no positive effect. The purpose of the study is a theoretical justification for the possibility of using different art forms as tools to unlock the possibilities and diversity of the art of food and filmmaking. Based on the study of various sources, it has been found that the topic of preserving the ethnic cultures of Russia is relevant and new, due to the unusual combination of the art of food and filmmaking. Hypothesis. It is suggested that the preservation and development of the country's ethnic cultures and intercultural ties is possible if best practices and achievements of food design as an essential part of people's culture will be applied while modelling different forms and spaces in film art. Results. Based on the results of the study, it can be concluded that the hypothesis put forward has historical evidence in the works of such scientists as: Kostomarov N.I., Orlovskaya A.V. and Pokhlebkin V.V. Based on their experience and knowledge the following is possible: formation of new approaches, serch for new solutions and development of new forms and spaces, using advances in food design, film art and people's culture.